(untitled) (Research, Society and Development, 2021)
The guarantee of access to justice is a fundamental right, provided for in the Federal Constitution, which established the principle of non-removal of jurisdiction, guaranteeing free access to the Judiciary, which supports the gratuitousness of justice. Law 13,105/15, when providing for Free Justice, established themes consolidated by jurisprudence and doctrine, however, it did not establish the criteria for granting it. Thus, the problem to be analyzed in this article is about the need or not to prove the insufficiency of resources and the absence of parameters in the legal system. The methodology adopted is bibliographic research, with a descriptive and deductive approach on the subject. To apply for the benefit, a declaration stating that it is low-sufficient is enough, thus demonstrating an ease. For this reason, some scholars defend that only the declaration of hyposufficiency will be granted with documents that prove their real financial situation, as the declaration has relative presumption. However, the attachment of these documents is not uniform, each magistrate has requested the attachment of documents according to what he believes to be sufficient and according to the specific case. There is, however, a minority in the jurisprudence that has judged as sufficient only the declaration of hypo-sufficiency. Note that each judge will use their own subjective and discretionary criteria, not having uniformity regarding the granting of the benefit of free justice, causing the law to be applied unequally and providing the feeling of legal uncertainty.